PENINGKATAN PROSES PEMBELAJARAN MUATAN IPS TEMA 4 MENGGUNAKAN MODEL MODEL KOOPERATIF TIPE GROUP INVESTIGATION SISWA KELAS IV MIN 3 KOTA PADANG - Salmiyanti, Salmiyanti; Erita, Yeni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Integrated thematic learning is an instructional approach that combines various subjects into a cohesive and meaningful educational experience for students. The purpose of this research is to describe the improvement of the Social Studies Content Learning Process Theme 4 Using Cooperative Models of the Group Investigation Type for Class IV MIN 3 Padang City Students. This research is a classroom action research using qualitative and quantitative approaches. The subjects in this study were students of Class IV MIN 3 Padang City, with a total of 26 students consisting of 15 girls and 11 boys. The results showed that the implementation of the learning process in the second cycle of teacher aspects with a percentage of 99% with very good qualifications. Whereas in the first cycle student component, the percentage value of 82.14% showed a very good increase. From the results of this study it can be concluded that the use of the GI type cooperative model can improve the learning process of social studies content for fourth grade elementary school students.